Development of a novel fermented pumpkin-based beverage inoculated with water kefir grains: a response surface methodology approach - Wee, Yin Koh; Uthumporn, Utra; Ahmad, Rosma; Mohd. Esah, Effarizah; Wan Ishak, Wan Rosli; Park, Yong-Ha (Springer Verlag, 2017)
Pumpkin (Cucurbita pepo) is well known for its health and nutritional benefits and is recommended for daily consumption. This is the first report on optimization and development of fermented pumpkin-based water kefir beverage. Optimum pumpkin puree and brown sugar concentrations were found at 22.28 and 9.07% w/v, respectively, were made into a pumpkin-based beverage and fermented with water kefir grains for 24 h at 32 C. The optimized fermented pumpkin-based water kefir beverage was found to be non-alcoholic, achieved good overall acceptability and high Lactobacillus, acetic acid bacteria and yeast cell viability of approximately 1012, 109 and 109 CFU mL-1, respectively. Overall, the optimized product attained superb technological characteristics and has the potential for industrial exploitation as a refreshing water kefir drink.